Gas Exchange in the Filamentous Cyanobacterium Nostoc punctiforme Strain ATCC 29133 and Its Hydrogenase-Deficient Mutant Strain NHM5 - Lindberg, Pia (American Society for Microbiology, 2004)
Nostoc punctiforme ATCC 29133 is a nitrogen-fixing, heterocystous cyanobacterium of symbiotic origin. During nitrogen fixation, it produces molecular hydrogen (H(2)), which is recaptured by an uptake hydrogenase. Gas exchange in cultures of N. punctiforme ATCC 29133 and its hydrogenase-free mutant strain NHM5 was studied. Exchange of O(2), CO(2), N(2), and H(2) was followed simultaneously with a mass spectrometer in cultures grown under nitrogen-fixing conditions. Isotopic tracing was used to separate evolution and uptake of CO(2) and O(2). The amount of H(2) produced per molecule of N(2) fixed was found to vary with light conditions, high light giving a greater increase in H(2) production than N(2) fixation. The ratio under low light and high light was approximately 1.4 and 6.1 molecules of H(2) produced per molecule of N(2) fixed, respectively. Incubation under high light for a longer time, until the culture was depleted of CO(2), caused a decrease in the nitrogen fixation rate. At the same time, hydrogen production in the hydrogenase-deficient strain was increased from an initial rate of approximately 6 μmol (mg of chlorophyll a)(−1) h(−1) to 9 μmol (mg of chlorophyll a)(−1) h(−1) after about 50 min. A light-stimulated hydrogen-deuterium exchange activity stemming from the nitrogenase was observed in the two strains. The present findings are important for understanding this nitrogenase-based system, aiming at photobiological hydrogen production, as we have identified the conditions under which the energy flow through the nitrogenase can be directed towards hydrogen production rather than nitrogen fixation.